2017
DOI: 10.1038/srep45470
|View full text |Cite
|
Sign up to set email alerts
|

Badger macrophages fail to produce nitric oxide, a key anti-mycobacterial effector molecule

Abstract: The European badger is recognised as a wildlife reservoir for bovine tuberculosis (bTB); the control of which is complex, costly and controversial. Despite the importance of badgers in bTB and the well-documented role for macrophages as anti-mycobacterial effector cells, badger macrophage (bdMφ) responses remain uncharacterised. Here, we demonstrate that bdMφ fail to produce nitric oxide (NO) or upregulate inducible nitric oxide synthase (iNOS) mRNA following Toll-like receptor (TLR) agonist treatment. BdMφ al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Different research groups have frequently observed the complete or partial failure of macrophages in producing NO − in cultures containing fetal bovine serum (FBS). The MDM from humans, cattle, sheep, goats, badgers, and ferrets in a culture containing FBS were found to be unable to produce a detectable level of NO − or approximately 20-to 50-fold less than macrophages from chickens (Denis, 1994;Dumarey et al, 1994;Arias et al, 1997;Ohki et al, 1999;Sacco et al, 2006;Zelnickova et al, 2008;Khalifeh et al, 2009;Guimarães et al, 2011;Azevedo et al, 2016;Bilham et al, 2017;Garcia et al, 2017). The FBS contains a considerable amount of immuno-regulatory cytokines and bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Different research groups have frequently observed the complete or partial failure of macrophages in producing NO − in cultures containing fetal bovine serum (FBS). The MDM from humans, cattle, sheep, goats, badgers, and ferrets in a culture containing FBS were found to be unable to produce a detectable level of NO − or approximately 20-to 50-fold less than macrophages from chickens (Denis, 1994;Dumarey et al, 1994;Arias et al, 1997;Ohki et al, 1999;Sacco et al, 2006;Zelnickova et al, 2008;Khalifeh et al, 2009;Guimarães et al, 2011;Azevedo et al, 2016;Bilham et al, 2017;Garcia et al, 2017). The FBS contains a considerable amount of immuno-regulatory cytokines and bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible to hypothesize, that evolutionary adaption of the badger to a subterranean lifestyle contributes to its tolerance of environmental dust inhalation. Further, a recent in vitro study demonstrated, that badger macrophages fail to produce nitric oxide (NO) [ 37 ]. This free radical is an important anti-mycobacterial effector molecule, and was previously shown to be upregulated in an in vivo rat model of silica inhalation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is produced through oxidation of l -arginine ( 50 ) in a reaction catalyzed by an inducible nitric oxide synthase (iNOS) ( 51 ). However, studies in badgers have revealed that blood monocyte-derived macrophages do not produce NO or upregulate iNOS expression following in vitro activation of macrophages ( 52 ). This intriguing finding might imply that badgers should lack the ability to control infection via the innate response, though there is no strong pathological evidence to support this.…”
Section: Pathogenesis Of Tuberculosis In Badgersmentioning
confidence: 99%